Association between chronic kidney disease and age-related macular degeneration: a Mendelian randomization study - Hou, Yawei; Liu, Qinglin; Xiao, Zhenwei; Li, Yameng; Tian, Xinyang; Wang, Zhenguo (Frontiers in Aging Neuroscience, 2024)
Purpose Observational studies have reported inconsistent results on the relationship between chronic kidney disease (CKD) and age-related macular degeneration (AMD). The primary objective of this study was to investigate the causal relationships between estimated glomerular filtration rate (eGFR), CKD, its common causes, and AMD among participants of European descent. Methods Genetic variants associated with eGFR, CKD and its common causes, encompassing diabetic nephropathy (DN), immunoglobulin A nephropathy (IgAN), and membranous nephropathy (MN) were obtained from previously published genome-wide association studies (GWAS) and FinnGen database. Summary statistics for early AMD, AMD, dry AMD, and wet AMD were acquired from the GWAS and FinnGen database. Inverse-variance-weighted (IVW) method was the main MR analysis. Sensitivity analyses were performed with Cochran’s Q, MR-Egger intercept, and leave-one-out analysis. In addition, RadialMR was utilized to identify and remove outliers. Results IVW results showed that CKD, eGFR were not associated with any type of AMD (p > 0.05). DN (OR: 1.042, 95% CI: 1.002–1.083, p = 0.037) and MN (OR: 1.023, 95% CI: 1.007–1.040, p = 0.005) were associated with an increased risk of earl AMD. DN (OR: 1.111, 95% CI: 1.07–1.154, p = 4.87 × 10−8), IgAN (OR: 1.373, 95% CI: 1.097–1.719, p = 0.006), and MN (OR: 1.036, 95% CI: 1.008–1.064, p = 0.012) were associated with an increased risk of AMD. DN (OR: 1.090, 95% CI: 1.042–1.140, p = 1.57 × 10−4) and IgAN (OR: 1.480, 95% CI: 1.178–1.858, p = 7.55 × 10−4) were associated with an increased risk of dry AMD. The risk of wet AMD was associated with DN (OR: 1.107, 95% CI: 1.043–1.174, p = 7.56 × 10−4) and MN (OR: 1.071, 95% CI: 1.040–1.103, p = 5.48 × 10−6). Conclusion This MR study found no evidence of causal relationship between CKD and AMD. DN, IgAN, and MN may increase risk of AMD. This findings underscore the importance of ocular examinations in patients with DN, MN, and IgAN. More studies are needed to support the findings of our current study.